Activation of NLRP3 inflammasome in hepatocytes after exposure to cobalt nanoparticles: The role of oxidative stress. (December 2020) - Feng, Sisi; Zhang, Zhenyu; Mo, Yiqing; Tong, Ruirui; Zhong, Zexiang; Chen, Zhong; He, Dan; Wan, Rong; Gao, Meiqin; Mo, Yiqun; Zhang, Qunwei; Huang, Yang
Abstract: With the increased use of nanomaterials and increased exposure of humans to various nanomaterials, the potential health effects of nanomaterials cannot be ignored. The hepatotoxicity of cobalt nanoparticles (Nano-Co) is largely unknown and the underlying mechanisms remain obscure. The purpose of this study was to exam the hepatotoxicity induced by Nano-Co and its potential mechanisms. Our results showed that exposure of human fetal hepatocytes L02 to Nano-Co caused a dose- and a time-dependent cytotoxicity. Besides the generation of reactive oxygen species (ROS) and mitochondrial reactive oxygen species (mtROS), exposure to Nano-Co also caused activation of NOD-like receptor protein 3 (NLRP3) inflammasome in hepatocytes. After silencing NLRP3, one component of NLRP3 inflammasome, expression by siRNA strategy, we found that upregulation of NLRP3-related proteins was abolished in hepatocytes exposed to Nano-Co. Using antioxidants to scavenge ROS and mtROS, we demonstrated that Nano-Co-induced mtROS generation was related to Nano-Co-induced NLRP3 inflammasome activation. Our findings demonstrated that Nano-Co exposure may promote intracellular oxidative stress damage, and mtROS may mediate the activation of NLRP3 inflammasome in hepatocytes exposed to Nano-Co, suggesting an important role of ROS/NLRP3 pathway in Nano-Co-induced hepatotoxicity. These results provide scientific insights into the hepatotoxicity of Nano-Co and a basis for the prevention and treatment of Nano-Co-induced cytotoxicity. Highlights: Exposure of hepatocytes to cobalt nanoparticles (Nano-Co) caused cell toxicity. Nano-Co caused ROS/mtROS generation and intracellular oxidative stress damage. Nano-Co caused NLRP3 inflammasome activation. Nano-Co-induced ROS/mtROS may be involved in NLRP3 inflammasome activation. ROS/NLRP3 pathway plays an important role in Nano-Co-induced hepatotoxicity.